2017
DOI: 10.1002/anie.201611058
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Trifluoromethyl‐Radical‐Induced Three‐Component Coupling of Boronic Esters with Furans

Abstract: In the presence of trifluoromethylsulfonium reagents, boronate complexes derived from 2‐lithio furan and non‐racemic secondary and tertiary alkyl or aryl boronic esters undergo deborylative three‐component coupling to give the corresponding 2,5‐disubstituted furans with excellent levels of enantiospecificity. The process proceeds via the reaction of boronate complexes with a trifluoromethyl radical, which triggers 1,2‐metallate rearrangement upon single‐electron oxidation. Alternative electrophiles can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 86 publications
2
21
0
Order By: Relevance
“…3 , Scheme a) . Furthermore, inspired by the intriguing reactivity of unsaturated boronate complexes, we showed that nucleophilic furyl‐derived boronate complexes 2 react with electrophiles in an enantiospecific three‐component coupling reaction (leading to 4 , Scheme a) . Key to the success of this process was the use of highly activated electrophiles, such as the Umemoto trifleoromethylating agent or carbocationic species.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 , Scheme a) . Furthermore, inspired by the intriguing reactivity of unsaturated boronate complexes, we showed that nucleophilic furyl‐derived boronate complexes 2 react with electrophiles in an enantiospecific three‐component coupling reaction (leading to 4 , Scheme a) . Key to the success of this process was the use of highly activated electrophiles, such as the Umemoto trifleoromethylating agent or carbocationic species.…”
Section: Methodsmentioning
confidence: 99%
“…[3] Furthermore,i nspired by the intriguing reactivity of unsaturated boronate complexes, [4] we showed that nucleophilic furyl-derived boronate complexes 2 react with electrophilesi na n enantiospecific three-componentc oupling reaction (leading to 4,S cheme1a). [5] Key to the success of this process was the use of highly activated electrophiles, such as the Umemoto trifleoromethylating agent [6] or carbocationic species. Interestingly, the trifluoromethylation reaction was found to proceed through as elf-initiated radical chain mechanism.I ndependently,S tudera nd our group have shown that electrophilic radicals add to vinyl boronate complexes 5 (Scheme 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furans can not only be used as key structural units in a number of biological active natural products, pharmaceuticals, and agrochemicals, but can also act as important precursors in the synthesis of acyclic, carbocyclic, and heterocyclic compounds . Owing to the reasons above, the substituted furans have played a crucial role in catalytic synthesis reactions in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Aggarwal et al further demonstrated that boron ate complexes of enantioenriched alkylboronic esters and furan-2-yllithium undergo stereospecific 1,2-metalate rearrangements in the reaction with the trifluoromethyl radical. [5] Importantly,s uch chiral secondary boronic esters are readily accessed by hydroboration, [6] by the Matteson approach, [7] and by reaction of boronic esters with Hoppese nantioselectively lithiated carbamates. [8] We considered using in situ generated vinyl boron ate complexes VI,derived from enantioenriched boronic esters V and vinyllithium, in ar adical polar crossover reaction with various alkyl iodides and report herein that this key transformation followed by oxidation offers anew route to a-chiral ketones.S uch chiral moieties are widespread in natural products and the development of synthetic routes to access enantioenriched a,a-disubstituted ketones is therefore of great importance.A lthough many protocols for auxiliarycontrolled asymmetric enolate reactions have been developed over the last decades, [9] the direct asymmetric alkylation of ketones is still highly challenging [10] and mostly transitionmetal catalysts are required.…”
mentioning
confidence: 99%